2016
DOI: 10.1155/2016/8640871
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cystectomy In-a-Bag of an Intact Cyst: Is It Feasible and Spillage-Free After All?

Abstract: This prospective study was conducted to assess the feasibility of laparoscopic cystectomy of an intact adnexal cyst performed inside a water proof endoscopic bag, aiming to avoid intraperitoneal spillage in case of cyst rupture. 102 patients were recruited. Two of them were pregnant. In 8 of the patients the lesions were bilateral, adding up to a total of 110 cysts involved in our study. The endoscopic sac did not rupture in any case. Mean diameter of the cysts was 5.7 cm (range: 2.3–10.5 cm). In 75/110 (68.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…They used the modified technique with laparoscopic bag, even in the group of women with borderline ovarian lesions, the rupture rate was 50% (one in a pregnant woman) with zero % leakage [12]. Also in the present study, Some ovarian cysts ruptured but in the presence of the endoscopic bag there was no spill of any content in cysts less than 6 cm .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…They used the modified technique with laparoscopic bag, even in the group of women with borderline ovarian lesions, the rupture rate was 50% (one in a pregnant woman) with zero % leakage [12]. Also in the present study, Some ovarian cysts ruptured but in the presence of the endoscopic bag there was no spill of any content in cysts less than 6 cm .…”
Section: Discussionsupporting
confidence: 50%
“…A previous study made Stelios Detorakis showed that the relative risk for rupture increases by 48% for every 1 cm increase in cyst diameter, while the relative risk for leakage increases by four folds respectively. From a clinical importance, the most important issue is not to prevent rupture of a cyst but to prevent its leakage [12].…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Shiota et al, comparison of 1,483 cases of benign ovarian cysts according to the cyst size showed no difference in the incidence of cyst rupture among patients with cyst sizes < 5 cm, 5 -10 cm, and > 10 cm (14), which confirm the results of the present study. In another study by Detorakis et al, studying the surgical outcome of 102 women with adnexal cysts with mean size of 5.7 cm (2.3 -10.5 cm) showed cyst rupture in 31.8% of the patients and 7.2% in masses > 8 cm (15). These authors concluded that laparotomy is the preferred method for large adnexal masses, but generally speaking, iatrogenic or accidental rupture and spillage of the adnexal mass contents are considered as an inevitable incidence during surgery and may occur both in laparoscopic and laparotomic approaches (4).…”
Section: Discussionmentioning
confidence: 96%
“…In another study by Shiota et al, comparison of 1483 cases of benign ovarian cysts according to the cyst size showed no difference in the incidence of cyst rupture among patients with cyst size < 5 cm, 5-10cm, and > 10 cm (14), which con rm the results of the present study. In another study by Detorakis et al, studying the surgical outcome of 102 women with adnexal cysts with mean size of 5.7 cm (2.3-10.5 cm) showed cyst rupture in 31.8% of the patients and 7.2% in masses > 8 cm (15). These authors concluded that laparotomy is the preferred method for large adnexal masses, but generally speaking, iatrogenic or accidental rupture and spillage of the adnexal mass contents are considered an inevitable incidence during surgery and may occur both in laparoscopic and laparotomic approaches (4).…”
Section: Discussionmentioning
confidence: 96%